A high performance electrochemical biosensor based on Cu2O–carbon dots for selective and sensitive determination of dopamine in human serum. Issue 67 (24th July 2015) - Huang, Qitong; Lin, Xiaofeng; Lin, Changqing; Zhang, Yong; Hu, Shirong; Wei, Chan
<x xml:space="preserve">Abstract</x> A green and facile method was developed by synthesizing a cuprous oxide–carbon dots/Nafion (Cu2O–CDs/NF) composite film for highly sensitive and reliable determination of dopamine (DA).